Description of the larva of Oulimnius echinatus Berthélemy (Coleoptera: Elmidae: Elminae) - Čiampor Jr., Fedor; Čiamporová-Zaťovičová, Zuzana; Kodada, Ján (Zootaxa, 2009)
The mature larva of Oulimnius echinatus Berthélemy is described for the first time, based on material from Mallorca (Spain). Morphologically the larva of O. echinatus resembles those of O. jaechi Hernando, Ribera & Aguilera and O. fuscipes (Reiche, 1879), from which it differs in the distinctly denser dorsal granulation, the less prominent setiferous tubercle on posterior angles of tergites and the absence of mesal setiferous tubercle on tergites and ventrites. We used for the first time scanning electron microscopy to describe the morphology of an Oulimnius larva. The genus Oulimnius Gozis occurs in Europe, North Africa and North America (Kodada & Jäch 2005; Jäch et al. 2006). To date, 16 species and subspecies have been described, although the systematic position of the two American species within the genus is open to question.